DESIGN OF AN AI-SUPPORTED PROTOTYPE APPLICATION FOR ASSESSING WRITING SKILLS IN TURKISH AS A FOREIGN AND SECOND LANGUAGE. - COŞKUN, Kadir; DURMUŞ, Mustafa (Turkbilig/Turkoloji Arastirmalari Dergisi, 2025)
Recent advancements in artificial intelligence technologies have introduced innovative educational approaches, making learning processes richer and more accessible. This study introduces an AI-supported web application that assesses the writing of learners of Turkish as a foreign or second language and functions seamlessly in hybrid and distance-learning settings. Within the developed application, instructors can create writing activities for learners in their classes, and learners can create texts using these activity guidelines and share them with instructors. Learners' written products are scored based on the activity guidelines using an analytical rubric, developed through artificial intelligence, covering form, content, and grammar. The rubric scores and artificial intelligence feedback obtained from the evaluation are presented to learners, who can revise their texts in line with the feedback they receive. Instructors can mark errors in completed learner texts, add explanations, and contribute to the system with rubric scores. In addition, the application was developed to create a dataset that instructors and institution managers can use when planning their teaching processes. It provides the compilation and recording of indicators such as the number of errors in learner texts, learner vocabulary, writing speed, word and sentence lengths on a process-based basis. It is believed that the effectiveness and sustainability of this model, which differs from current practices by aiming to provide a learning environment where learners and instructors come together to teach Turkish as a foreign and second language by taking advantage of the potential offered by artificial intelligence, will be increased with future research.